Pendampingan Pendirian Madrasah Unggulan Bilingual Global: Implementasi Peningkatan Mutu Berkelanjutan Pendidikan pada MI Ma’arif 04 Desa Gentasari Kecamatan Kroya Kabupaten Cilacap: Mentoring for the Establishment of a Global Bilingual Leading Madrasah: Implementation of Continuous Quality Improvement of Education at MI Ma'arif 04, Gentasari Village, Kroya District, Cilacap Regency - Tobroni, Imam; Fathurohim, Fathurohim; Habib, Muhamad; Muliyah, Pipit (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This article discusses a community service program aimed at supporting the establishment of a globally competitive bilingual flagship madrasah at MI Ma'arif 04 in Gentasari Village, Kroya Sub-district, Cilacap. This program is part of an effort to enable the madrasah to compete with other educational institutions, particularly in addressing global education challenges. It also focuses on empowering the community in education by leveraging existing potential to develop a high-quality, competitive madrasah. The program involves active participation from the entire madrasah community and broad public engagement, including various stakeholders. The mentoring activities cover numerous aspects, ranging from planning and preparing facilities and infrastructure to developing a globally-oriented bilingual curriculum, teacher training, and public outreach and school promotion. This program is expected to improve the quality of education at MI Ma'arif 04 Gentasari in a sustainable manner, thereby generating positive impacts on social change and community development.